Pengembangan Lembar Kerja Peserta Didik Berbasis Project Based Learning Di Kelas Tiga - Na'imah, Lailatun; Fauziyah, Nur; Khikmiyah, Fatimatul (Universitas Muhammadiyah Gresik, 2024)
The aim of this research is to use LKPD-based learning media with the PjBL learning model with valid, effective and practical fraction material. The research method used by researchers in this study uses the ADDIE paradigm, which is an abbreviation for